AGAMA DAN FENOMENA TREND HIJAB - Ratih Himamatu Azizah Tannisyafolia (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2021)
Hijab has meaning as a person’s religious identity and behavior. But for some people the hijab is not only a body covering for women, but the hijab is used a fashion trend. This study will discuss how the meaning of hijab and what underlies female student using hijab in several campuses in kediri with the of Muhammadiyah, Nahdatul Ulama, Wahidiyah and how the practice of religious orientation is carried out by hijab-wearing female student in the city of Kediri. this reseach uses pierre bordieou’s theory of social practice and Raymond F. Paloutzian intrinsic extrinsic concept. The study used a qualitative descriptive method. Data collection techniques with field studies, and libraries. The result of the research student have different orientations in the meaning of hijab and religion. In social practice, there is a habitus that influences the reason why female students wearing hijab. Hijab is an extrinsic religious behavior because using religion she lives with hijab as a fashion trend. However, for students who have intrinsic orientation, people who live based on religion or use the hijab in accordance with religious law. Family background and different Islamic religious sect also affect the orientation and religious behavior of female students.